1992
DOI: 10.1007/bf00168162
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant rejection and cholestasis: comparison of technetium 99m-diisopropyl iminodiacetic acid hepatobiliary imaging with liver biopsy

Abstract: To determine whether the scintigraphic evaluation of technetium-99m diisopropyl iminodiacetic acid (DISIDA) uptake and excretion can distinguish among liver transplant patients with biopsy evidence for rejection, cholestasis or neither condition, we reviewed scintigrams and biopsies in 36 patients. There were 76 scintigrams with corresponding biopsies. Uptake and excretion were graded from image data on scales reflecting normal through severely abnormal values. Biopsies were evaluated for findings of cholestas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
(23 reference statements)
0
8
0
1
Order By: Relevance
“…Brunot et al demonstrated a close relation between early biopsy results and liver uptake function measured by HBS, implying that HBS is valuable in distinguishing graft rejection from cholestasis (89). In contrast, others reported that HBS can distinguish between normal grafts and those experiencing rejection or cholestasis but not between biliary complications and rejection (85,90).…”
Section: Clinical Use Of Hbs In Liver Transplantationmentioning
confidence: 96%
“…Brunot et al demonstrated a close relation between early biopsy results and liver uptake function measured by HBS, implying that HBS is valuable in distinguishing graft rejection from cholestasis (89). In contrast, others reported that HBS can distinguish between normal grafts and those experiencing rejection or cholestasis but not between biliary complications and rejection (85,90).…”
Section: Clinical Use Of Hbs In Liver Transplantationmentioning
confidence: 96%
“…Excretion of technetiumlabeled imidoacetate compounds has been proposed for the study of functional hepatic reserve in chronic liver disease [ 1 ] and in liver transplant patients [2][3][4][5][6]. Uptake of HIDA derivatives is useful for in vitro functional analysis of hcpatocytes in culture [7], and scintigraphic analysis of these radionuclides has been reported in a study of experimental cold and warm liver ischaemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiography, magnetic resonance imaging, immunologic markers, positron-emission scintigraphy, and other radioisotopic techniques are being considered as potential screening tests for rejection after heart transplantation (29)(30)(31). Hepatobiliary nuclear imaging has been used in liver transplant recipients to help differentiate normal recipients from those with rejection and/or cholestasis (32).…”
Section: Discussionmentioning
confidence: 99%